Heteroatom-doped electrodes for all-vanadium redox flow batteries with ultralong lifespan. Issue 1 (6th December 2017) - Huang, Peng; Ling, Wei; Sheng, Hang; Zhou, Yan; Wu, Xiaopeng; Zeng, Xian-Xiang; Wu, Xiongwei; Guo, Yu-Guo
Abstract : The heteroatom-doped graphite felt electrode with prominent hydrophilicity presents excellent electroactivity towards V 2+ /V 3+ and VO 2+ /VO2 +, and dramatically extends the energy efficiency of vanadium redox flow batteries towards 1000 cycles with 0.003% reduction per cycle. Abstract : The phosphorus and fluorine codoped graphite felt electrodes with prominent hydrophilicity present excellent electroactivity towards V 2+ /V 3+ and VO 2+ /VO2 +, elevate the discharging ability up to 250 mA cm −2 and dramatically extend the energy efficiency of vanadium redox flow batteries towards 1000 cycles with 0.003% reduction per cycle.